Sonographic morphology scores (SMS) for differentiation between benign and malignant adnexal masses - Wanapirak C. (2014)
To determine the sensitivity and specificity of a scoring system for distinguishing between benign and malignant adnexal masses and to detect threshold scores for prediction of malignant ovarian tumors.